Buffalo land: an authentic account of the discoveries, adventures, and mishaps of a scientific and sporting party in the wild West ... - Webb, W. E. (Geo. Maclean, 1874)
A description principally of western Kansas and eastern Colorado, including notes on the paleontology of Kansas. Much on hunting in the West, especially buffalo hunts, but also elk, antelope, turkeys, prairie chickens, quail, etc. Information on Indian tribes, their leaders and customs, military forts, exploring, characters met during his travels, etc. He talks at some length about his meeting with Wild Bill Hickok. He elaborates on the technique of "creasing" wild horses during chases to capture them. This is done by shooting at the horse with a rifle bullet that just creases the horse's skull, and renders the horse unconscious for a time sufficient to capture it.
A description principally of western Kansas and eastern Colorado, including notes on the paleontology of Kansas. Much on hunting in the West, especially buffalo hunts, but also elk, antelope, turkeys, prairie chickens, quail, etc. Information on Indian tribes, their leaders and customs, military forts, exploring, characters met during his travels, etc. He talks at some length about his meeting with Wild Bill Hickok. He elaborates on the technique of "creasing" wild horses during chases to capture them. This is done by shooting at the horse with a rifle bullet that just creases the horse's skull, and renders the horse unconscious for a time sufficient to capture it.
Keywords: Paleontology / Kansas.; Hunting / West (U.S.); West (U.S.) / Description and travel.